Osteopontin, a Key Mediator Expressed by Senescent Pulmonary Vascular Cells in Pulmonary Hypertension. Issue 9 (September 2016) - Saker, Mirna; Lipskaia, Larissa; Marcos, Elisabeth; Abid, Shariq; Parpaleix, Aurelien; Houssaini, Amal; Validire, Pierre; Girard, Philippe; Noureddine, Hiba; Boyer, Laurent; Vienney, Nora; Amsellem, Valerie; et al.
Abstract : Objective—: Senescent pulmonary artery smooth muscle cells (PA-SMCs) may contribute to the pathogenesis of pulmonary hypertension by producing secreted factors. The aim of this study was to explore the role in pulmonary hypertension of extracellular matrix proteins released by senescent PA-SMCs. Approach and Results—: Polymerase chain reaction array analysis of human PA-SMCs undergoing replicative senescence revealed osteopontin upregulation, which mediated the stimulatory effect of senescent PA-SMC media and matrix on PA-SMC growth and migration. Osteopontin was upregulated in lungs from patients with chronic obstructive pulmonary disease or idiopathic pulmonary arterial hypertension. Prominent osteopontin immunostaining was noted in PA-SMCs that also stained for p16 at sites of vascular hypertrophy, and lung osteopontin levels correlated closely with age. Compared with younger mice, 1-year-old mice displayed higher lung osteopontin levels, right ventricular systolic pressure, pulmonary vessel muscularization, and numbers of PA-SMCs stained for p16 or p21 and also for osteopontin. No such changes with age were observed in osteopontin −/− mice, which developed attenuated pulmonary hypertension during hypoxia. Compared with cultured PA-SMCs from young mice, PA-SMCs from 1-year-old mice grew faster; a similar fast growth rate was seen with PA-SMCs from young mice stimulated by matrix or media from old mice. Differences between old/young mouse PA-SMC growth rates were suppressed by antiosteopontin antibodies. PA-SMCs from osteopontin −/− mice grew more slowly than did wild-type PA-SMCs; they were stimulated by wild-type PA-SMCs media and matrix, and this effect was stronger with PA-SMCs from older versus younger mice. Conclusions—: Osteopontin is a key mediator released by senescent PA-SMCs and contributing to pulmonary hypertension progression. Abstract : Supplemental Digital Content is available in the text.